Pelatihan Microsoft Excel Guna Menunjang Tugas Administrasi Perawat Poliklinik Rumah Sakit Dok II Jayapura - Alienra Davry Nanda Kadun MT; Rahmat Nurjaman; Dwi Astuti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Administration in the healthcare sector needs to prioritize thoroughness, accuracy, and responsiveness. The polyclinics of Jayapura Dok II Hospital play an important role in outpatient care. Nevertheless, these health facilities are still constrained due to the low utilization of technology for administrative functions. This training partnered with Dok II Hospital to improve nurses’ skills in using Microsoft Excel for administrative tasks. Modules designed from the training made in accordance with the nurses’ administrative tasks.